Evolução das significações em trajectórias de droga-crime (II): novos sentidos para a intervenção psicológica com toxicodependentes? - Celina Manita (2001)
The results of a study about the evolution of meanings in the trajectory of drug addicts and drug-crime trajectories are presented and analysed, completing the information and analysis started in a previous paper. Furthermore, there is a discussion of their implications for the psychological intervention with drug addicts, analysing both the influence of meanings and narrative organisation of senses in the orientation of the actions of the individuals, and the role of meanings within the context of psychotherapy. At this level the constructivistic and social constructionism approaches are mentioned, as well as the self-organisation theories, more specifically the autopoietic subject theory. The usefulness of the narrative therapies and the biograme method is stressed.